PENGARUH CITRA MEREK, PROMOSI PENJUALAN, SALURAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK (STUDI PADA TOKO DAN+DAN DI DUTA HARAPAN) - Olivia Yoestin Agriyang Gadi; Donant Alananto Iskandar (Ultima Management : Jurnal Ilmu Manajemen, 2020)
Abstract- The purposes of the study were to know and to analyze the effect of brand image, sales promotion, and distribution channels partially and simultaneously to the purchase decision of cosmetic products in DAN+DAN stores in Duta Harapan Bekasi. The sample used in this study were 100 respondents and the sampling method was non-probability sampling which is purposive sampling.This research is a quantitative associative, associative research is a research that aims to determine the effect or also the relationship between two or more variables. That is brand image, sales promotion and distribution channels as independent variables and purchase decision as dependent variable.The result of this research indicates that brand image has significant effect to purchase decision. That is proven by the unstandardized coefficient value of 0.348, it means between brand image and purchase decision has a quite strong positive relationship.Whereas, sales promotion and distribution channels have also affected purchase decision, which is shown by the regression unstandardized coefficient value of 0.178 In addition, distribution channels variable has a positive relationship to purchase decision that is illustrated by the coefficient value of 0.198. Finally, between brand image, sales promotion, and distribution channels have 39.7 percent contribution in order to increase purchase decision of DAN+DAN STORE in Duta Harapan Bekasi, the remaining percentage was contributed by other variables which was not studied in this research. Keywords: Brand Image, Sales Promotion, Distribution Channels, Purchase Decision.